The red notebook - Laurain, Antoine (Gallic Books, 2015)
Bookseller Laurent Letellier comes across an abandoned handbag on a Parisian street and feels compelled to return it to its owner. The bag contains no phone or contact information. But a small red notebook with handwritten thoughts and jottings reveals a person that Laurent would very much like to meet. Without even a name to go on, how is he to find one woman in a city of millions?--Page [4] cover.